Jewish Environmental Ethics for the Anthropocene: An Integrative Approach - Tirosh-Samuelson, Hava (The journal of Jewish thought & philosophy, 2022)
This article argues that the Judaic understanding of creation care is a potent response to the challenges of the Anthropocene because Judaism acknowledges that humans have much in common with all other created beings, while respecting their alterity, and because Judaism insists on human responsibility toward and care of the created world. However, Jewish environmental ethics of care and responsibility could be greatly enriched if it incorporates the insights of the feminist ethics of care, ecofeminism, and environmental virtue ethics, three discourses to which Jewish environmentalists have paid limited attention so far, even though the secularization of Judaism in the twentieth century has impacted these discourses.